The adoption of IOT in the Malaysian construction industry: Towards construction 4.0 - Farah Salwati, Ibrahim; Muneera, Esa; Abdul Rahimi, Abdul Rahman (UTHM, 2021)
The construction industry is one of the most significant sectors in Malaysia, specifically in terms of its contribution to the Malaysian Gross Domestic Product (GDP) and facilitation of other industries to enhance their productivity outcome by constructing buildings and facilities for them. However, the process of constructing buildings and facilities will take a long period of time if done according to conventional practices. Due to this circumstance, the establishment of the Internet of Things (IoT) in construction development is beneficial to improve productivity levels and reduce the construction time as well as the cost. Hence, this paper intends to review the adoption of IoT in Malaysia’s construction industry towards Construction 4.0. In conjunction with that, the use of IoT in terms of construction technology such as BIM, smart communication, sensor, big data, augmented reality, location services and remote operation during the construction process has made a massive impact on the monitoring of the construction process, especially in reducing the risk of construction error, defects, and avoiding construction delay. The proper adoption of IoT in the Malaysian construction industry will give a huge positive impact to the construction industry and encourage it to grow and compete with other developing countries. This paper is noteworthy to the Malaysian construction industry, especially for the key players in the construction industry to raise their awareness regarding the benefits of adopting IoT for their future projects.